2020
DOI: 10.1042/bsr20191136
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-101-3p inhibits fibroblast-like synoviocyte proliferation and inflammation in rheumatoid arthritis by targeting PTGS2

Abstract: Objective: Rheumatoid arthritis (RA) is the most frequently occurring inflammatory arthritis. The present study was performed to characterize the role of microRNA-101-3p (miR-101-3p) and prostaglandin-endoperoxide synthase 2 (PTGS2) in inflammation and biological activities of fibroblast-like synoviocytes (FLSs) in RA. Methods: Initially, miR-101-3p and PTGS2 expression in RA tissues of RA patients and RA rats was detected by qRT-PCR and Western blot analysis. Rat model of type II collagen-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 40 publications
(45 reference statements)
0
20
0
Order By: Relevance
“…8 miR-101-3p is dysregulated and plays a role in synovial fibroblast-like cells in patients with rheumatoid arthritis. 9 Interestingly, many miRNAs have been shown to have regulatory effects on HIE. For instance, miR-499-5p exhibits neuroprotective effects on HIE in neonatal rats by blocking C-reactive protein.…”
Section: Introductionmentioning
confidence: 99%
“…8 miR-101-3p is dysregulated and plays a role in synovial fibroblast-like cells in patients with rheumatoid arthritis. 9 Interestingly, many miRNAs have been shown to have regulatory effects on HIE. For instance, miR-499-5p exhibits neuroprotective effects on HIE in neonatal rats by blocking C-reactive protein.…”
Section: Introductionmentioning
confidence: 99%
“…As a mature form of miR-101, decreased levels of miR-101-3p have been shown to exert tumor suppressor functions in numerous malignant tumors, and to regulate proliferation, invasion and metastasis ( 20 , 21 ). However, to the best of our knowledge, the role of miR-101-3p in inflammatory diseases has been rarely reported.…”
Section: Discussionmentioning
confidence: 99%
“…In non-tumor diseases, miR-101-3p has been shown to be significantly upregulated in the plasma of patients with adult onset Still's disease (AOSD) and to positively correlate with the expression of inflammatory mediators ( 20 ). Moreover, miR-101-3p also affects other inflammation-related diseases, such as rheumatoid arthritis ( 21 ) and heart transplant recipients with histologically-verified acute cellular rejection ( 22 ). However, to the best of our knowledge, there are limited studies available investigating the effects of miR-101-3p on the inflammatory response post-SIC.…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al 51 demonstrated that miR‐27b directly inhibits HIPK2 expression that would lead to chondrocyte apoptosis and, thus, ameliorate the development of RA. Recently, Wei et al 52 ascertained that miR‐101‐3p reduces joint swelling and the rheumatoid factors in rats with RA by downregulating PTGS2, as evidenced by inhibited FLS proliferation and inflammation. Studies have verified that miRNAs are expressed in both the synovial tissue and the circulating blood in patients with RA, meaning that miRNA may serve as a biomarker for RA.…”
Section: Ra‐related Mirna Lncrnamentioning
confidence: 99%